Yo service remembered, receives award from UMP - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 27 December 2021 - Two individuals named ‘Yo’ received an award from Universiti Malaysia Pahang (UMP) for their services and sacrifices after rescuing a family of flood victims living in Tanah RTK Ekonomi Sri Damai in the recent flood disaster in Pahang.